GABAB receptor antibodies in paraneoplastic cerebellar ataxia - Jarius, Sven; Steinmeyer, Florian; Knobel, Astrid; Streitberger, Kaspar; Hotter, Benjamin; Horn, Sigrun; Heuer, Heike; Schreiber, Stephan; Wilhelm, Tabea; Trefzer, Uwe; Wildemann, Brigitte; Ruprecht, Klemens (Journal of neuroimmunology, 2013)
Autoantibodies to the gamma-aminobutyric acid-B (GABAB) receptor were recently described in patients with limbic encephalitis presenting with early or prominent seizures. We report on a 64-year-old man with malignant melanoma who during adjuvant therapy with interferon (IFN)-alpha developed cerebellar ataxia. Indirect immunofluorescence on brain tissue sections revealed high-titer (1:20,000) IgG1 serum autoantibodies to the cerebellar molecular and granular layer, which were confirmed to be directed against GABAB receptor in a cell-based assay. This case highlights cerebellar ataxia in the absence of seizures as a clinical manifestation of GABAB receptor autoimmunity and extends the spectrum of tumors underlying this condition to malignant melanoma. IFN-alpha therapy may have contributed to the development of autoimmunity in this patient.
Gesehen am 25.03.2021